2015
DOI: 10.4049/jimmunol.1501097
|View full text |Cite
|
Sign up to set email alerts
|

Th Cell Diversity in Experimental Autoimmune Encephalomyelitis and Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is believed to be initiated by myelin-reactive CD4+ Th cells. IL-12 polarized Th1 cells, IL-23 polarized Th17 cells, and exTh17 cells (Th17 cells that acquire Th1 characteristics) have each been implicated in autoimmune pathogenesis. It is currently debated whether Th cells that can drive the development of demyelinating lesions are phenotypically diverse or arise from a single lineage. In the current study we assess the requirement of IL-12 or IL-23 stimulation, as well as Th plasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 28 publications
2
47
0
2
Order By: Relevance
“…Thus, future T cell-targeted therapies for patients with severe cryptococcal CNS disease will need to identify critical windows of T cell functions and carefully weigh their pathological versus beneficial effects. These data showing the pathological potential of IFN-␥-producing T cells in the CNS during C. neoformans meningoencephalitis are supported by notable damaging roles of CD4 ϩ and CD8 ϩ T cells in the CNS during infections, including cerebral malaria (63)(64)(65), viral encephalitis (66), toxoplasmosis (67)(68)(69), tuberculosis meningitis (27), and immunological disorders such as multiple sclerosis (70). However, a similar paradigm exalting paradoxical roles for T cells has only recently begun to emerge in the study of cryptococcal infections.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, future T cell-targeted therapies for patients with severe cryptococcal CNS disease will need to identify critical windows of T cell functions and carefully weigh their pathological versus beneficial effects. These data showing the pathological potential of IFN-␥-producing T cells in the CNS during C. neoformans meningoencephalitis are supported by notable damaging roles of CD4 ϩ and CD8 ϩ T cells in the CNS during infections, including cerebral malaria (63)(64)(65), viral encephalitis (66), toxoplasmosis (67)(68)(69), tuberculosis meningitis (27), and immunological disorders such as multiple sclerosis (70). However, a similar paradigm exalting paradoxical roles for T cells has only recently begun to emerge in the study of cryptococcal infections.…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported that Th17 plasticity is indispensable for development of experimental autoimmune encephalomyelitis (EAE) (16), colitis (13), and diabetes (19). In contrast, one study has shown that stable Th17 cells, which are derived from IL-12 KO mice, are capable of inducing the same severe EAE as plastic Th17 cells (20). Our results demonstrate that Th17 plasticity enhances Th17 pathogenicity and is required for a severe ocular surface immunoinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that although the serum levels of IFN‐γ and TNF‐α were very low in PDR patients, after activation by TCR signal, the levels multiplied many‐fold and significantly higher than in NPDR and normal controls, which suggest an abnormal Th1 response in the peripheral blood cells from DR patients. Based on the previous studies, which showed proinflammatory effect of Th1 response in autoimmune disorders , we speculated that Th1 cells might play a proinflammatory role in the pathogenesis of PDR through secretion of IFN‐γ and TNF‐α. The important role of IL‐6 in DR development involves the regulation of immune responses, the stimulation of angiogenesis and the increase of vascular permeability .…”
Section: Discussionmentioning
confidence: 98%
“…Aberrant autoreactivated T‐helper (Th) cells, including Th1 cells, Th2 cells, and Th17 cells, are believed to play an important role in many autoimmune diseases, whose effector mechanisms include production of proinflammatory cytokines that initiate and amplify inflammation, and also provide help to autoreactive B cells . IFN‐γ‐producing Th1 cells are believed to be involved in the pathogenesis of autoimmune diseases, such as multiple sclerosis (MS) , rheumatoid arthritis (RA) . Th2 cells primarily produce IL‐4, IL‐10, and IL‐13, and are responsible for the pathogenesis of allergic diseases .…”
Section: Introductionmentioning
confidence: 99%